Soluble and bound peroxidases from papaya fruit - da Silva, Elisete [UNESP]; Lourenco, Euclides J. [UNESP]; Neves, Valdir Augusto [UNESP] (Elsevier, 1990)
Soluble and bound peroxidases were isolated from the pulp of ripening papaya fruit. During papaya ripening, soluble and bound peroxidase activities increased 2.5- and 4.2-fold, respectively. Soluble peroxidase was purified 59-fold by ammonium sulphate precipitation and chromatography on Sephadex G-25, DEAE-cellulose and Sephadex G-100. Bound peroxidase was purified 140-fold by ammonium sulphate precipitation and chromatography on Sephadex G-100 and DEAE-cellulose. Polyacrylamide gel electrophoresis of the purified preparations revealed that both enzymes were highly purified by the procedures adopted. The soluble and bound forms had a Mr of 41 000 and 54 000, respectively. Soluble and bound peroxidases showed optimum activity at pH 6.0 and 5.5, respectively, and were inhibited by p-chloromercuribenzoate, iodoacetamide, N-ethylmaleimide, potassium cyanide and Fe2+. Soluble peroxidase was activated by ammonium sulphate and this activation was prevented by cyanide. © 1990.
Keywords: Carica papaya; Caricaceae; enzyme properties.; papaya fruit; peroxidase; ripening